The Effectiveness of SimBucket-Based Interactive E-LKPD with STAD in Enhancing Students’ Conceptual Understanding - Aditiya Wahyuni; Desy Hanisa Putri; Rosane Medrianti (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
In order to improve students' conceptual grasp of alternative energy, this study examined the viability and efficacy of integrating a SimBucket-based interactive E-LKPD with the Student Teams Achievement Division (STAD) cooperative learning paradigm. The ADDIE model was used in the research's R&D methodology. Thirty-six senior high school students participated. Expert validation sheets, conceptual comprehension assessments, and student response questionnaires were used to gather data, which were then analyzed using normalized gain (N-Gain) and descriptive statistics. The designed E-LKPD received an 87.14% validation score. indicating that it was highly feasible. Student responses reached 90.76%, demonstrating excellent usability and engagement. Furthermore, the average N-Gain score of 0.83 (high category) indicated substantial improvement in students’ conceptual understanding. These findings demonstrate that integrating SimBucket simulations with E-LKPD and the STAD model effectively supports conceptual learning. This study contributes to digital physics education by providing an innovative learning medium that visualizes abstract concepts while promoting active and collaborative learning.